2004
DOI: 10.1038/sj.onc.1208268
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of human Int-6 impairs mitosis progression and inhibits cyclin B–Cdk1 activation

Abstract: The Int-6 protein has been originally identified as the product of a mouse gene being a frequent integration site of the mouse mammary tumour virus. Here, we show that reducing Int-6 expression by RNA interference in HeLa cells markedly alters mitosis progression. Defects in spindle formation, chromosome segregation and cytokinesis were observed. These abnormalities of mitosis completion are correlated with an inhibition of cyclin BCdk1 kinase activity, due to a prolonged inhibitory phosphorylated state of Cdk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 40 publications
3
33
0
Order By: Relevance
“…MAD2L1, which was negatively regulated by eIF3e (Figures 3 and 4), is a component of the mitotic spindle attachment checkpoint; its dysfunction, through either reduced or increased expression, can cause aberrant chromosome segregation, and hence contribute to malignancy, in mammalian cells (Michel et al, 2001;Sotillo et al, 2007). Inhibition of eIF3e expression was shown previously to delay mitotic progression in human cells (Morris and Jalinot, 2005); our findings suggest that elevated MAD2L1 expression may contribute to this phenotype.…”
Section: Discussionsupporting
confidence: 54%
“…MAD2L1, which was negatively regulated by eIF3e (Figures 3 and 4), is a component of the mitotic spindle attachment checkpoint; its dysfunction, through either reduced or increased expression, can cause aberrant chromosome segregation, and hence contribute to malignancy, in mammalian cells (Michel et al, 2001;Sotillo et al, 2007). Inhibition of eIF3e expression was shown previously to delay mitotic progression in human cells (Morris and Jalinot, 2005); our findings suggest that elevated MAD2L1 expression may contribute to this phenotype.…”
Section: Discussionsupporting
confidence: 54%
“…In fission yeast, Yin6 enables proteasome activity by promoting the nuclear import of its Rpn5 subunit, and Yin6 inactivation causes defective cyclin B and securin degradation, leading to mitotic anomalies (Yen and Chang, 2000;Yen et al, 2003). In human cells, we showed that INT6 silencing also leads to mitosis alteration due to defects in spindle formation, chromosome segregation and cytokinesis (Morris and Jalinot, 2005).…”
Section: Introductionmentioning
confidence: 79%
“…We have reported previously that silencing of INT6 in HeLa cells does not modify duration of the G1 phase (Morris and Jalinot, 2005), thus providing an indication that the onset of DNA replication is not altered. To test possible defects during the replication process, we first measured the stability of MCM7 in control or INT6-depleted cells synchronized at the G1/S transition by a double thymidine block (Figure 5a).…”
Section: Int6 Regulates Mcm7 Stability S Buchsbaum Et Almentioning
confidence: 99%
“…eIF3e is a cytoplasmic protein, but is also detected in the nucleus in many organisms including plants (Desbois et al, 1996;Watkins and Norbury, 2004;Yahalom et al, 2001). The role of nuclear eIF3e is still unclear, although it has been associated with (i) control of 26S proteasome activity (Yen et al, 2003), (ii) the COP9 signalosome (Yahalom et al, 2001), another regulator of proteolysis, (iii) human T-cell leukemia virus transcriptional transactivator (HTLV Tax) Tax activity, (iv) the 'nuclear speckle' proto-oncogene products Rfp and PML (Desbois et al, 1996;Morris-Desbois et al, 1999), and (v) spindle organization (Morris and Jalinot, 2005;Yen and Chang, 2000). Although eIF3e is not essential for global translation initiation in Schizosaccharomyces pombe (Bandyopadhyay et al, 2000;Zhou et al, 2005), there is good evidence that eIF3e plays a pivotal role in translation (Asano et al, 1997;Bandyopadhyay et al, 2002Bandyopadhyay et al, , 2000.…”
Section: Introductionmentioning
confidence: 99%